2015
DOI: 10.1016/j.ajpath.2014.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human Complement Factor H Prevents Age-Related Macular Degeneration–Like Retina Damage and Kidney Abnormalities in Aged Cfh Knockout Mice

Abstract: Complement factor H (CFH) is an important regulatory protein in the alternative pathway of the complement system, and CFH polymorphisms increase the genetic risk of age-related macular degeneration dramatically. These same human CFH variants have also been associated with dense deposit disease. To mechanistically study the function of CFH in the pathogenesis of these diseases, we created transgenic mouse lines using human CFH bacterial artificial chromosomes expressing full-length human CFH variants and crosse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 39 publications
5
77
0
Order By: Relevance
“…5 This new role of FH is endorsed by a recent study showing that the expression of human complement FH prevents AMD-like retina damage and kidney abnormalities in aged CFH − / − mice. 31 In conclusion, we have found a new intriguing function of the complement inhibitor FH in apoptotic cell clearance and handling of potential autoantigens (nucleosomes). FH becomes internalized by apoptotic cells and induces intracellular cleavage of C3, which becomes exposed on the cell surface in form of the potent opsonin iC3b, providing an additional removal signal to phagocytes.…”
Section: Discussionmentioning
confidence: 83%
“…5 This new role of FH is endorsed by a recent study showing that the expression of human complement FH prevents AMD-like retina damage and kidney abnormalities in aged CFH − / − mice. 31 In conclusion, we have found a new intriguing function of the complement inhibitor FH in apoptotic cell clearance and handling of potential autoantigens (nucleosomes). FH becomes internalized by apoptotic cells and induces intracellular cleavage of C3, which becomes exposed on the cell surface in form of the potent opsonin iC3b, providing an additional removal signal to phagocytes.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, the internalization of FH into apoptotic cells with ensuing functional effects may be of particular importance in this tissue. A recent study confirmed the importance of FH in development of AMD and SLE by revealing that the expression of human FH is able to prevent AMD‐like retinal damage and kidney abnormalities in aged CFH −/− mice . The previously suggested relationship between chronic kidney disease and AMD, two seemingly disparate diseases, is thus confirmed.…”
Section: Fh Internalization By Apoptotic Cells Leads To Increased Opsmentioning
confidence: 66%
“…[21] An animal model using transgenic mouse with high expression of CFH, demonstrated a dose-dependent protective effect in the function and structure of both eye and renal abnormalities. [22] In addition, the sharing of common cardiometabolic risks (hypertension, diabetes, dyslipidemia, and tobacco) [23] and pathogenic pathways (atherosclerosis, endothelial dysfunction, oxidative stress, inflammation, altered genetic polymorphisms, complement system dysfunction, and Klotho gene pathway) between these 2 diseases strengthens the supposition of this association. [35,8] Clinically, this association has been demonstrated from findings of several epidemiological studies, such as the Blue Mountains Eye Study, [9] case–control subset study of NHANES III, [10] and the Beaver Dam Eye Study.…”
Section: Discussionmentioning
confidence: 99%